Use of Bone Morphogenetic Protein Among Patients Undergoing Fusion for Degenerative Diagnoses in the United States, 2002–2012 - Martin, Brook I. (Spine J, 2014)
BACKGROUND CONTEXT: Use of Bone Morphogenetic Protein (BMP) as an adjunct to spinal fusion surgery proliferated following Food and Drug Administration (FDA) approval in 2002. Major safety concerns emerged in 2008. PURPOSE: To examine whether published concerns about the safety of BMP altered clinical practice. STUDY DESIGN/SETTING: Analysis of the National Inpatient Sample from 2002 through 2012. PATIENT SAMPLE: Adults (age >20) undergoing an elective fusion operation for common degenerative diagnoses, identified using codes from the International Classification of Diseases, 9(th) revisions, Clinical Modification (ICD-9-CM). OUTCOME MEASURES: Proportion of cervical and lumbar fusion operations, over time, that involved BMP. METHODS: We aggregated the data into a monthly time series and reported the proportion of cervical and lumbar fusion operations, over time, that involved BMP. Auto Regressive Integrated Moving Average, a regression model for time series data, was used to test whether there was a statistically significant change in the overall rate of BMP use following a FDA Public Health Notification in 2008. The study was funded by federal research grants, and no investigator had any conflict of interests. RESULTS: Use of BMP in spinal fusion procedures increased rapidly until 2008, involving up to 45.2% of lumbar and 13.5% of cervical fusions. BMP use significantly decreased following the 2008 FDA Public Health Notification and revelations of financial payments to surgeons involved in the pivotal FDA approval trials. For lumbar fusion, the average annual increase was 7.9 percentage points per year from 2002 to 2008, followed by an average annual decrease of 11.7 percentage points thereafter (p = <0.001). Use of BMP in cervical fusion increased 2.0% per year until the FDA Notification, followed by a 2.8% per year decrease (p = 0.035). CONCLUSIONS: Use of BMP in spinal fusion surgery declined subsequent to published safety concerns and revelations of financial conflicts-of-interest for investigators involved in the pivotal clinical trials.